Tree species diversity driven by environmental and anthropogenic factors in tropical dry forest fragments of central Veracruz, Mexico - Guadalupe Williams_Linera; Francisco Lorea-Hernández (Biodiversity and Conservation, 2009)
We examined vegetation structure and woody species diversity in relation to 14 environmental and anthropogenic factors in ten tropical dry forest (TDF) fragments in central Veracruz, Mexico. The basal area of the canopy (30.2 ± 2.11 m2/ha) and under- story (1.96 ± 0.12 m2/ha) trees was similar, but density (1,014 ± 104 and 2,532 ± 227 individuals/ha, respectively) differed among sites. We recorded 98 canopy, 77 understory, and 60 seedling species. Richness was 24?45 species per site, Fisher?s alpha and Shannon?s indices increased with site altitude. Chao Jaccard indices revealed high species turnover, and a consistently higher similarity within the sites at the lowest and within the highest elevation sites. Ordination identified altitude, aspect, slope, water proximity, cattle and trails as significant explanatory variables of species patterns, and showed that sites at lower elevations were clearly separated from the other sites. Environmental heterogeneity alone did not control species diversity distribution, but species were affected by environmental filters at different stages in their life cycle, e.g., water proximity was significant for sap- lings and seedlings but not for adults. Anthropogenic disturbances act synergistically, e.g., trails played a key role in determining structure and tree diversity patterns. An important finding is that human disturbance diminishes species diversity in this TDF, but sites at lower elevations were more disturbed and less diverse, therefore we need to study how environmental factors would act if there were no anthropogenic disturbance.